Perioperative care of a patient with zygomatic implant placement assisted by a dynamic real-time navigation system (动态导航引导下行穿颧种植术1例的围手术期护理) - GUAN Zhaolan (管兆兰); YIN Xiaoqing (尹小青); XIE Lingling (谢玲玲) (中西医结合护理)
This paper summarized the perioperative nursing management for a patient with zygomatic implant placement assisted by a dynamic real-time navigation system. Key nursing issues should be taken into consideration included: preoperative psychological counseling and treatment of nasosinusitis; intraoperative airway management and nursing cooperation for using dynamic real-time navigation system; postoperative pain control, ice compress, oral care, prevention of complications of paranasal sinus, eyes, face and maxillary sinus, incision wound care, dietary guidance, health education about maintenance of false teeth. By implementing instant and temporary screw-retained dental prothesis within 24 hours, it could realize initial stability of implant and repair backward recovery of masticatory function. Besides, effective oral biological function can be rebuilt and there was no occurrence of complications. (本文总结1例动态实时导航引导下行解剖学为导向的穿颧种植(ZAGA)术患者围术期护理经验, 护理要点包括术前心理疏导, 指导患者积极治疗鼻窦炎; 术中呼吸道管理, 应用导航仪的护理; 术后疼痛、冰敷护理, 口腔护理, 鼻窦、眼部、面部、上颌窦并发症管理及切口观察, 饮食指导及义齿的使用和维护。种植体初期稳定性良好, 修复后咀嚼功能恢复, 获得有效的口腔生物功能重建, 无并发症发生。)